2022
DOI: 10.1038/s41598-022-16864-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact on the reduction of CO2 emissions due to the use of telemedicine

Abstract: Digital health can reduce CO2 emissions thanks to telemedicine and access to digital test results and medical reports. However, the environmental impact of digital health activity is not well known. Here, we show that telemedicine reduces CO2 emissions. We found a net total of 6,655 tons of CO2 emissions decrease through a reduction in patient travel to surgeries and medical clinics thanks to the alternatives of digital appointments and digital access to test results and medical reports, which avoid the need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Eight studies were conducted in the United Kingdom, 7 in the United States, and 2 in Spain, with the remainder in France, Ireland, Sweden, Canada, and Portugal. One study examined the impact of video consulting at a national level across different health care specialties [ 58 ]. Two other studies attempted to extrapolate from the analysis of the reduction in carbon emissions in 1 telemedicine service to the national level [ 39 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies were conducted in the United Kingdom, 7 in the United States, and 2 in Spain, with the remainder in France, Ireland, Sweden, Canada, and Portugal. One study examined the impact of video consulting at a national level across different health care specialties [ 58 ]. Two other studies attempted to extrapolate from the analysis of the reduction in carbon emissions in 1 telemedicine service to the national level [ 39 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies used videoconferencing software combined with digital imaging [ 61 , 62 ]. In 1 instance, both telephone and videoconferencing were used to deliver virtual services [ 42 ], and in 4 other studies, patients were given the option of either telephone or audiovisual/video consulting [ 43 , 46 , 53 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this approach contributes to reducing a patient's environmental impact by reducing the need for travel. Consequently, this article is relevant to the Special Topic "One Health" as it highlights the potential benefits of telehealth in improving patient outcomes and reducing environmental impacts, as shown in [21]. In addition to reducing the time and travel burden associated with participation, remote technology, and decentralization tools can also help increase patient enrollment in cancer clinical trials as suggested by the findings of Adams et al [22].…”
Section: Insights Into the Candidate Papers And Best Papersmentioning
confidence: 99%
“…Virtual care, is defined as the remote diagnosis and treatment of patients by means of telecommunications technology 8 . It can reduce emissions from patient travel and resource utilization from in‐person interactions across a variety of specialties 9–12 . Virtual care can also be more convenient and cost‐effective for patients and improve healthcare access for rural and remote communities 7,8,13 .…”
Section: Introductionmentioning
confidence: 99%